Peranan Pendidikan Agama Kristen Bagi Pembinaan Anak Tunagrahita - Rotua Julianovia Rebecca Hutagalung (Sekolah Tinggi Teologi Jaffray Jakarta, 2019)
Christian Religious Education has a role in fostering mentally retarded children so that they know God in their daily lives, and apply that education through their actions towards God, self, and others. Looking at the results of a research survey it appears that BEFORE retarded children receive education at C1 level SLB, many parents and even the environment are less accepting of their existence; Shyness and low self-esteem are seen in mentally retarded children; the development of children's abilities in trying to help themselves is still difficult; adaptation to the environment is still difficult; parental responses to educators in implementing PAK are still not emphasizing; the development of thinking, emotions, behavior, speech is still lacking. Seeing the condition of mentally retarded parents and children as above, they really need a Christian educator who can support, direct, educate, and foster them with great love and patience. For this reason a Christian educator needs to understand techniques in teaching, using appropriate teaching methods, getting to know the character of each of his students, even teachers must be able to train and equip them with the teachings of the Word of God so that through this parents can accept the existence of their children, and children can also do something by yourself. Through education given to mentally retarded children they also experience the development of thinking, emotions, behavior, and speaking. Parents also have an important role in developing, educating, training and teaching them with love. Parents can perform their role properly and correctly if he accepts all of their children's existence in learning, and parents must also be a driving force for their lives in learning and playing so that the child's development can continue to be monitored and children can live independently in carrying out their responsibilities as a child students. The purpose of writing this article is firstly, when mentally retarded children receive a Christian Religious Education they can apply the Word of God through their attitudes toward God, such as praying, singing, and listening to the Word. Second, besides praying, singing, they can help each other help, love. Third, based on the education provided they can take care of themselves, pay respect to older people. Fourth, their recognition of the Lord Jesus is clearer and educators must provide examples and examples for them. The discussion in the writing of this article is about the introduction of mentally retarded children; Christian Religious Education for the development of mentally retarded children; the role of parents in handling mental retardation children.